2018
DOI: 10.5993/ajhb.42.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Weight Gain/Loss among Emerging Adults with Obesity

Abstract: Results suggest that the perceived ability to control one's behaviors and overcome barriers, self-efficacy, and mood are important in weight-related behaviors, weight, and weight loss success among emerging adults, especially those enrolled in college.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…This indicates that other variables, such as personal lifestyle choices (as evidenced by the 6FQ) might be of greater interest in explaining interindividual differences in SREBQ. In line with previous studies (Campos-Uscanga et al, 2017;Johnson and Annesi, 2018), our results suggested that individuals with overweight and obesity exhibited lower levels of self-regulation than individuals with normal weight or underweight. Further, women exhibited better self-regulation of eating behavior than men.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that other variables, such as personal lifestyle choices (as evidenced by the 6FQ) might be of greater interest in explaining interindividual differences in SREBQ. In line with previous studies (Campos-Uscanga et al, 2017;Johnson and Annesi, 2018), our results suggested that individuals with overweight and obesity exhibited lower levels of self-regulation than individuals with normal weight or underweight. Further, women exhibited better self-regulation of eating behavior than men.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, it has been suggested that the ability to choose and competently apply strategies of self-regulation may explain the gap between intention and behavior (Allan et al, 2011;Gellert et al, 2011). For instance, individuals lacking self-regulation in the sense of reduced impulse control, could be at higher risk of weight gain (Campos-Uscanga et al, 2017;Johnson and Annesi, 2018). In patients with obesity, studies revealed deficits in broad executive functions, which are strongly correlated with successful selfregulation (Dohle et al, 2018;Yang et al, 2018).…”
Section: Self-regulation Of Eating Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…37 In that study, however, frequent fast-food, overeating and skipping breakfast were the primary eating behaviour factors surrounding weight gain. 37 Conversely, participants cited healthy eating as more challenging when parents and family members brought 'unhealthy' foods into the home, including snacks and 'junk food' . The adolescents expressed frustration with parents for how their actions could be simultaneously supportive and unsupportive.…”
Section: Differences Specific To Femalesmentioning
confidence: 79%
“…Certain individual barriers identified by the students, such as an insufficient budget for the purchase of healthy foods, have also been pointed out by other authors [ 5 , 32 , 50 ]. However, this limited budget interacts with the perception that healthy foods are more expensive, and is an environmental barrier that is most likely, as Marquis [ 51 ] has pointed out, to encourage prioritization of the purchase of cheap and fast foods as opposed to healthy and less affordable products [ 52 ]. In relation to the latter, the greater accessibility, through vending machines, of ultra-processed and prepared products that are cheaper in the university environment interacts with a lack of individual willpower, making it difficult to make healthy food purchases.…”
Section: Discussionmentioning
confidence: 99%